(untitled) (Linguostylistic Studies, 2016)
The article highlights the contribution of Academician M. Kravchuk into the development of the Ukrainian mathematical terminology system created during the period of «Ukrainization» processes in the early twentieth century. The study highlights the (extra) intralinguistic factors that influenced the development of terminology in that period. The analysis of special lexicon used to describe mathematical concepts in scientific and popular scientific publications has provided opportunities to differentiate lexical-thematic groups of mathematical terms. Attention is drawn to the linguistic features of the terminology under the study. It has been revealed that the mathematical terms in the M. Kravchuk’s publications reflect the complex system of concepts. Working in the field of the theoretical mathematics, the scientist used the terms from the theories, laws, formulas, theorems, hypotheses, phenomena in this field. The study shows that most of them have been created using the word building means and patterns of the Ukrainian language, and by terminologization of the basic vocabulary words. Key words: Ukrainian mathematical terminology, term, terminology, thematic group, term-phrase, scientific concept. References